The mitochondrial genome of Cofana yasumatsui (Hemiptera: Cicadellidae: Cicadellinae) - Zhong, Li-Kun (Mitochondrial DNA B Resour, 2020)
The complete mitochondrial genome of Cofana yasumatsui (Hemiptera: Cicadellidae: Cicadellinae) is sequenced. Based on annotation, the mitochondrial genome is 15,019 bp, has an A + T content of 77.2% (A = 42.0%, T = 35.2%, G = 10.0%, C = 12.8%), which is the classical structure for insect mitogenome. All PCGs started with ATN, except ATP8 and ND5 starting with TTG. All PCGs used TAN as stop codon, except ND5 stopping with single T. The phylogenetic relationship of C. yasumatsui clustered together with Cicadella viridis, Homalodisca coagulata, Homalodisca vitripennis, and Bothrogonia ferruginea from Cicadellinae. This is identical with the result of the traditional taxonomy.